Pengaruh Motivasi, Pengawasan, Dan Budaya Kerja Terhadap Kinerja Karyawan Pada PT. Nagalan Maju Bersama - Susi Donna Sinaga; Nora Anisa Br. Sinulingga (Junal Ilmu Manajemen, 2018)
In the t test, there is a motivation t-test value of 2.448 greater than the t-table value of 2.119 and sig t of 0.027 smaller than alpha 0.05. There is a t-test value of 3.375 is greater than the t-table value of 2.119 and the sig t of 0.013 is smaller than the alpha of 0.05. And there is a Work Culture t-test value of 5.590 is greater than the t-table value of 2.119 and sig t of 0.033 is smaller than alpha 0.05. From these results it can be concluded that motivation, supervision, and work culture have a positive and significant effect on employee performance. The simultaneous hypothesis test shows that motivation, supervision and work culture together are positive and significant influences on employee performance. This is seen through the F-calculated value of 5.695 greater than the F-table at alpha 5% has a value of 3.238 with a significance level of 0.008 less than 0.05. On the test of the coefficient of determination can be seen the R-Square value of 0.732. This means that 73.2% of the variation in the value of Employee Performance can be explained by the role of Motivation, Supervision, and Work Culture. And the remaining 26.8% is influenced by other variables.